Financial vs Non-Financial Gifts and Workers' Performance: An Experimental Analysis of Reciprocity in the Workplace - Thompson, Megan (Organisational Psychology, 2022)
Background and research orientation, rationale and objectives. Gift giving or reciprocity is widely used in organisations as an attempt to further improve employee performance and productivity, which is ultimately believed to result in higher levels of organisational performance and success. Reciprocity theory, or the gift exchange view, assumes that employees and organisations pursue that which is in their own material self-interest. Reciprocity research is, however, still largely dominated by research focusing on the impact of financial rewards, despite major reward theories, models and approaches that increasingly emphasise the importance of both financial and non-financial rewards in attraction, employee engagement or motivation and retention. The aim of the current research study was to investigate the extent to which employees reciprocate discretionary effort, as indicated by higher levels of productivity, after receiving either a financial or non-financial gift or reward. Moreover, the impact of receiving either a financial or non-financial reward on perceived levels of both employee motivation and job satisfaction was measured, as well as to determine reward preference which was considered more motivating and satisfying. Research approach. The present study made use of an experimental research approach, more so, a controlled field experiment in a naturally occurring work environment. Both quantitative and qualitative data were collected from employees to measure their perceived levels of motivation and job satisfaction. Productivity data was provided by the organisation employing the employees to determine the impact of the financial or non-financial reward. Composite questionnaires consisting of open-ended questions and Likert-type questions were distributed using a convenience, non-probability sampling approach. All completed questionnaires, along with the provided productivity data, were analysed using descriptive statistics, inferential statistics and content analysis. Main findings. Results of the research study indicated a significant difference in employees perceived level of motivation and job satisfaction after receiving a financial or non-financial gift. Thus, employees experienced greater levels of motivation and job satisfaction after receiving a financial or non-financial gift. Results furthermore showed that employees were more productive after receiving the gift, although the productivity did not shift any different whether they received the financial or non-financial gift. Thus, employee reciprocated discretionary effort after receiving a gift. A statistically significant association was found between the gift employees received and the gift they desired, with the likelihood of receiving a particular gift and desiring that specific gift not being random, but rather due to psychological feelings of appreciation.